Ocular Health of Octodon degus as a Clinical Marker for Age-Related and Age-Independent Neurodegeneration - Chang, Lily Y. -L.; Palanca-Castan, Nicolas; Neira, David; Palacios, Adrian G.; Acosta, Monica L. (Frontiers in Integrative Neuroscience, 2021)
The aging process and age-related diseases such as Alzheimer’s disease (AD), are very heterogeneous and multifactorial, making it challenging to diagnose the disease based solely on genetic, behavioral tests, or clinical history. It is yet to be explained what ophthalmological tests relate specifically to aging and AD. To this end, we have selected the common degu (Octodon degus) as a model for aging which develops AD-like signs to conduct ophthalmological screening methods that could be clinical markers of aging and AD. We investigated ocular health using ophthalmoscopy, fundus photography, intraocular pressure (IOP), and pupillary light reflex (PLR). The results showed significant presence of cataracts in adult degus and IOP was also found to increase significantly with advancing age. Age had a significant effect on the maximum pupil constriction but other pupil parameters changed in an age-independent manner (PIPR retention index, resting pupil size, constriction velocity, redilation plateau). We concluded that degus have underlying factors at play that regulate PLR and may be connected to sympathetic, parasympathetic, and melanopsin retinal ganglion cell (ipRGC) deterioration. This study provides the basis for the use of ocular tests as screening methods for the aging process and monitoring of neurodegeneration in non-invasive ways.